Enhancing Corporate Environmental Performance Through Green Process Innovation: A Sustainable Business Approach - Ningly, Ira; Rahmadhani, Sari (Jurnal Akuntansi, 2025)
This study aims to examine the factors that affect the company's Corporate Environmental Performance (CEP) and examine the role of Green Process Innovation (GPI) on the relationship between Environmental Management Accounting (EMA), Green Transformational Leadership (GTL), and Green Human Resource Management (GHRM) towards CEP. This quantitative research method uses data from the annual reports of raw material sector companies listed on the IDX for 2019-2023. Data were analyzed using path analysis using PLS-SEM. The direct effect results showed that EMA, GTL, and GPI significantly increased CEP, while GHRM did not impact CEP. GTL and GHRM affect GPI, while EMA does not affect GPI. The mediation test results show GPI's role in mediating the relationship between GTL and GHRM towards CEP. These findings indicate the importance of environmentally friendly processes in increasing CEP. This research supports NRBV theory and emphasizes sustainable natural resource management to achieve long-term competitive advantage.